Evaluation of the influence of aeration on the discharge capacity and flow induced vibrations of Piano Key Weir spillways - Lombaard, Jaretha (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.